2018
DOI: 10.1038/s41598-018-24647-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Steam Burns Severity using Raman Spectroscopy on ex vivo Porcine Skin

Abstract: Skin burns due to accidental exposure to hot steam have often been reported to be more severe than the ones occurring from dry heat. While skin burns due to flames or radiant heat have been thoroughly characterized, the mechanisms leading to steam burns are not well understood and a conundrum still exists: can second degree burns occur without destruction of the epidermis, i.e. even before first degree burns are detected? Skin permeability is dependent both on temperature and on the kinetic energy of incoming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…To assess the risk of injury of human skin from contacting hot surfaces, there is a relatively extensive literature [1][2][3][4][5][6][7][8][9][10] and thresholds have been specified in standards and guidelines [11,12]. On the other hand, the risk of injury to the oral mucosa from hot foodstuffs has been little studied.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the risk of injury of human skin from contacting hot surfaces, there is a relatively extensive literature [1][2][3][4][5][6][7][8][9][10] and thresholds have been specified in standards and guidelines [11,12]. On the other hand, the risk of injury to the oral mucosa from hot foodstuffs has been little studied.…”
Section: Introductionmentioning
confidence: 99%
“…Upon dermal exposure, TiO 2 NPs may penetrate through the stratum corneum (SC) as the first defensive layer with pore sizes varying from less than 0.4 nm to approximately 100 nm via transcellular, intercellular, and transappendageal routes. Hair follicles may provide an alternative route for the transdermal delivery of TiO 2 NPs across the SC . Human forearm in vivo experiments showed that 20 nm cubic and 100 nm acicular TiO 2 penetrated the outermost layer of SC .…”
Section: Introductionmentioning
confidence: 99%
“…It is an important tool for determining structural information of solid and liquid media and chemical bonding changes. RS as a nondestructive technique has been applied in analytical chemistry, skin studies, , food analysis, and detection of exogenous substances in latent fingerprints where it is important not to harm the samples. Another technique is the near-infrared spectroscopy (NIRS) that uses the NIR radiation (780–2500 nm) and the light attenuation by the sample to understand its chemical constitution and physical parameters. , The use of the NIR region allows a greater penetration depth for biomedical applications, meaning it is useful for probing bulk materials; however, the tradeoff is the technique sensitivity .…”
Section: Introductionmentioning
confidence: 99%